2020
DOI: 10.3390/foods9050581
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing Conditions on the Flavor Profiles of Mulberry (Morus alba Linn) Fruits Using Instrumental Flavor Analysis and Descriptive Sensory Analysis

Abstract: The purpose of this study was to identify the influence of drying method on flavor profiles of mulberry fruit using purge and trap (P&T) flavor extraction followed by gas chromatography–mass spectrometry (GC-MS) and descriptive sensory analysis using a highly trained sensory panel. Mulberry fruit samples were prepared at different temperatures (−20, 0, 50, and 60 °C). The results showed that more diverse volatile compound profiles were produced overall and had increased levels of benzaldehyde, nonanal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Monoterpenes gradually decreased while alcohols, esters and aldehydes increased during fruit ripening ( Hijaz et al., 2020 ), which may explain the relatively high levels of monoterpenes in pulp samples from a new very early-season pummelo cultivar. 2-methylheptane and 4-methyloctane were exclusively detected in LYZ pulp ( Figure 4B and Table 3 ), where 2-methylheptane was one of the major oil components of Amomum Subulatum fruits ( Agnihotri et al., 2012 ), and 4-methyloctane was identified as one of the main volatile constitutes in mulberry ( Morus alba ) ( Hwang and Kim, 2020 ) and black rice ( Oryza sativa ) during storage ( Choi et al., 2019 ). Hexanal (3.51-8.51), described as green and grassy odor, was the most abundant volatile compound in pummelo pulp samples ( Table 3 ), which was consistent with the results of ‘Huangjin’, ‘Sanhong’ and ‘Dongshizao’ ( Zhu et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoterpenes gradually decreased while alcohols, esters and aldehydes increased during fruit ripening ( Hijaz et al., 2020 ), which may explain the relatively high levels of monoterpenes in pulp samples from a new very early-season pummelo cultivar. 2-methylheptane and 4-methyloctane were exclusively detected in LYZ pulp ( Figure 4B and Table 3 ), where 2-methylheptane was one of the major oil components of Amomum Subulatum fruits ( Agnihotri et al., 2012 ), and 4-methyloctane was identified as one of the main volatile constitutes in mulberry ( Morus alba ) ( Hwang and Kim, 2020 ) and black rice ( Oryza sativa ) during storage ( Choi et al., 2019 ). Hexanal (3.51-8.51), described as green and grassy odor, was the most abundant volatile compound in pummelo pulp samples ( Table 3 ), which was consistent with the results of ‘Huangjin’, ‘Sanhong’ and ‘Dongshizao’ ( Zhu et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…2-methylheptane was one of the major oil components of Amomum Subulatum fruits (Agnihotri et al, 2012), and 4methyloctane was identified as one of the main volatile constitutes in mulberry (Morus alba) (Hwang and Kim, 2020) and black rice (Oryza sativa) during storage (Choi et al, 2019). Hexanal (3.51-8.51), described as green and grassy odor, was the most abundant volatile compound in pummelo pulp samples (Table 3), which was consistent with the results of 'Huangjin', 'Sanhong' and 'Dongshizao' (Zhu et al, 2020).…”
Section: Volatile Profile Of Lyz Pulpmentioning
confidence: 99%
“…However, two recent studies reported on the effectiveness of both techniques. For example, SBSE was used in the spray-dried soursop (Annona muncata; Neta et al, 2019), and distillation under reduced pressure was employed in dried mulberry (Morus alba L.; Hwang and Kim, 2020).…”
Section: Analysis Of Volatile Compounds In Dehydrated Fruitsmentioning
confidence: 99%
“…The drying of mulberry fruits at either 50 or 60°C was reported by Hwang and Kim (2020), which generated 30 volatile compounds. Of these, 12 volatile compounds were found in both fresh and dried fruits, respectively.…”
Section: Mulberry (Morus Alba L)mentioning
confidence: 99%
“…Since ancient times, different varieties of mulberry have been used in Asian countries, both as food (fruit) and in medicine (fruit, bark, leaves) [19]. Mulberry (Morus alba L.) fruits are most popular in East Asian countries such as Korea, China, Japan and Thailand, but are also consumed worldwide [20]. Due to the presence of polyphenols (such as phenolic acids (up to ~30 mg/kg fw), flavanol derivatives (from 55.62 to 432.38 mg/kg fw), and anthocyanins (up to ~3000 mg/kg fw)), polysaccharides, alkaloids, flavonoids, essential amino acids, and vitamins, white mulberry fruits are well known for their health-promoting properties, including anticoagulant, antioxidant, anti-diabetic, anti-obesity, anti-inflammatory, anti-carcinogenic, prokinetic, and neuroprotective effects [12,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%